The growth improvement of Grammatophyllum scriptum (Lindl.) Bl. in vitro plantlet using photoautotrophic micropropagation system - Aries Bagus Sasongko; Asruwaidah Fatumi; Ari Indrianto (Universitas Gadjah Mada, 2016)
To improve the growth of Grammatophyllum scriptum (Lindl.) Bl. in vitro plantlet, a photoautotrophic micropropagation system (PMS) was developed by growing in vitro plantlet on VW medium with varying concentration of sucrose (0, 5, 10, and 20 g/L) and additional carbon dioxide from the air (bottle covered with cap or filter). The result showed that the leaf length would increase up to 6.5 cm with PMS and it would keep growing by the adding of 5 g/L sucrose. Average number of leaves increased by 6.7 strands with PMS and the addition of sucrose increased the average quantity of leaves up to 7.7 strands. Average number and root length would increase with PMS and would even increase more with 5 g/L sucrose addition. PMS with 5 g/L sucrose can increase chlorophyll a and b concentration. The number of stomata per unit area in PMS was lower than closed culture. This shows that PMS can increase the growth of G. scriptum in vitro plantlet and the growth increase would be effective if it is combined with sucrose addition.